Relasi Elite, Sub-Elite, dan Masyarakat Desa dalam Mempertahankan Dinasti Keluarga Masra di Desa Gapurana Kabupaten Sumenep: Studi pada Rezim H. Andiwarto Tahun 2013-2019 - Ruth Agnesia Sembiring; Mishbahul Khoiri (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2021)
This research focuses on the relation of elite H. Andiwarto with sub-elite and village community in maintaining Masra family dynasty for village head position. Masra family dynasty has run for a long time. For 150 years, Masra family descendants occupy the village head position. The survival of Masra family dynasty in the Gapurana Village Government is studied in the relation of H. Andiwarto, who is Masra descendant with sub-elite and village community to maintain Masra family descendant dynasty as a village head. This research used a qualitative method with descriptive research type. The elite theory proposed by Suzanne Keller was used to analyze the relation of elite, sub-elite, and the community. This theory has 4 (four) indicators: the governing elite, the ruling elite, the not ruling elite, and the community. Based on these indicators and the results of this research, the relation built by H. Andiwarto in maintaining Masra family dynasti consists of three relations: relation with the political elite, relation with economic elite, and relation with the social elite. The political elite’s relationship is vital in maintaining the Masra family descendant dynasty. In contrast, the relation between the economic elite and the social elite supports relations for keeping the legitimacy of the village community towards Masra descendants.